Matxin - Urretabizkaia, Joseba (Tolosa : Xibarit, 2020)
Matxin Labaien tolosar pintorearen gaineko liburua.
Testua euskaraz eta gaztelaniaz
Keywords: Labaien, Matxin; Euskal pintoreak -- XX. m; Monografiak